TEACHERS’ COMPETENCE AREAS: CONSTITUTIONAL STAGE - Afanas, Aliona (International Journal of Innovative Technologies in Social Science, 2021)
The article addresses the issue of teachers' competence areas, identified during the constatative pedagogical experiment. The scientific analysis of the competence concept targeted towards the elaboration of the operational framework of professional development competencies, implemented within the constatative pedagogical experiment. Also, the experimental data contributed to the identification of the areas of teachers’ competence at the level of the education system and process. The constatative experiment involved 888 subjects divided into two samples: the training sample and the control sample. The article presents each competence area results obtained within the two samples: training and control ones. The evaluation of the competence areas was performed based on the evaluation criteria established for the competencies such as managerial; relational; design and planning, specialized cognitive; teaching-learning; evaluation and monitoring. During the experiment, several research methods were used, such as theoretical, empirical and interpretive methods. The identification of the competence areas was made by applying a questionnaire addressed to teachers during the continuous professional training courses.